Proposing an Integrated Research Framework for Connectivism: Utilising Theoretical Synergies - Boitshwarelo, Bopelo (International Review of Research in Open and Distributed Learning, 2011)
Connectivism is receiving acknowledgement as a fresh way of conceptualising learning in the digital age. Thus, as a relatively new instructional framework, it is imperative that research on its applicability and effectiveness in a variety of educational contexts is advanced. In particular, a high premium should be placed on context-specific research that is aimed not only at developing general principles but also at improving practice in local settings. Thus, developmental research approaches become imperative and as such it becomes increasingly necessary to have models that would assist scholars to understand the learning ecologies of connectivism. This paper therefore proposes a research framework for connectivism that integrates approaches commonly used in online learning environments. The paper integrates the theories of online communities of practice, design-based research, and activity theory to construct a research framework that is characterised by a synergistic relationship between them. It demonstrates the viability of the model by using an example of how it was operationalised in one research project. The framework, whose potential strength derives from integrating already established theoretical constructs, is presented as a proposal with the intention that it will be critiqued, tried, and improved upon where necessary and ultimately become part of the menu of other tools that serve connectivism research.